Management of Antithrombotic in Endoscopic Procedures - Suseno, Dwi; Syam, Ari Fahrial (Jurnal Penyakit Dalam Indonesia, 2018)
The use of antithrombotic medicine has increased along with the growing number of cardiovascular disease in the world. Endoscopy procedure often done to the patients who use antithrombotic medicine. Eventhough most of endoscopies are safe for those patients, there are some main things related to antithrombotic treatment management that have to be noted such as the kind of antithrombotic that being used, stratification of bleeding risk on the procedure, the risk of future thromboembolic, and the process of antithrombotic treatment re-initiation. So that, patient’s safety in undergoing endoscopy procedure is guaranteed.